ANALISIS DETERMINAN YANG MEMPENGARUHI PAJAK DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Ali Afif; Febriati Febriati; Rizky Fakhrul Yahya (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The central government has delegatedto each regional government the power and authority to manage and control national government programs and the interests of local communities in accordance with laws and regulations (independent jurisdiction). Inflation is a process in which prices continue to rise. Since rising commodity prices affect inflation, it isimportant to know more about the relationship between inflation and the sustainability of entertainment and its impact on local revenue through taxes. If so, according to the entertainment tax data of Bengkayang County, it is still far from the target even if used as a standard. Findings in recent years have shown that many recreational facilities, especially recreational facilities, must be maintained with local tax revenue. The aim of this study is to analyze the impact of tax incentives on entertainment tax using inflation as a control variable. The type of research used is quantitative. The sampling method used was a random sampling method. The population and sample of this study are entrepreneurs in the entertainment sector in Bengkayang District.